Soldier-Artist of the Great Reconnaissance : John C. Tidball and the 35th Parallel Pacific Railroad Survey - Tidball, Eugene C., 1930- (Book collections on Project MUSE., 2004)
Soldier-Artist of the Great Reconnaissance recaptures the Whipple expedition's trials and triumphs as it documents the unusual talents of one of its most versatile members."--Jacket.